Peasant families and milk production systems in the Anaime canyon (Colombia) - Martínez Restrepo, Gloria Lucía (2023)
The characterization of farm and household systems in the Anaime River basin in the Cajamarca - Tolima municipality was the objective of this study. 53 randomized surveys were applied. The survey covered human, social, physical, financial and natural resources. The typification showed three groups of farms: group 1 had a low proportion of land with a significant economic activity dedicated to crops (51.5%), group 2 with equitable economic activity between the livestock and agricultural component (50 %) and group 3 with a large amount of land devoted to livestock (60 %). Group 2 and 3 have three hectares of land have little land dedicated to conservation, in contrast group 3 has a high significance in this land use. Milk production generates a significant monetary income for families, as well as serving as a protein product based on their diet.